Growth and development of Gnathostoma spinigerum (Nematoda: Gnathostomatidae) larvae in Mesocyclops aspericornis (Cyclopoida: Cyclopidae) - Sanpool Oranuch; Intapan Pewpan M; Janwan Penchom; Sadaow Luxkhana; Thanchomnang Tongjit; Maleewong Wanchai (Parasites & Vectors, 2011)
Abstract Background Gnathostoma spinigerum larva is pathogenic, causing gnathostomiasis in humans and certain animals, and is prevalent mainly in Asia. Growth and development of Gnathostoma spinigerum larvae in the cyclopoid copepod Mesocyclops aspericornis, the first intermediate host, were examined. Results When newly hatched, ensheathed second-stage larvae (L2) were ingested by M. aspericornis, they immediately appeared exsheathed in the stomach of M. aspericornis. They then penetrated the stomach wall and entered the body cavity, where they immediately metamorphosed to a stunted form with the body length/width ratio equal to the early third-stage larvae (EL3) up to 2 h after being ingested. During metamorphosis, the anterior spine-like structure of L2 transformed into unequal transparent lips. The larvae moulted into EL3 in the body cavity of the copepod at around day 5-7 post-infection. Minute cuticular striations were seen on the whole body, with prominent single-pointed spines on the anterior part of the body. The head bulb had four rows of hooklets and two lateral trilobed lips. The size of EL3 in copepods continuously increased towards day 12 and showed a negative correlation to their density per copepod (R = -0.881, P < 0.05 for body length, and R = -0.906, P < 0.05 for body width). Conclusions The results revealed for the first time that M. aspericornis, one of the most abundant freshwater copepods in Thailand, is a suitable first intermediate host for G. spinigerum. High susceptibility of M. aspericornis suggests its importance for the maintenance of the life cycle of G. spinigerum in Thailand.